Optimization of Increasing Teacher Engagement through Strengthening Self-Efficacy, Interpersonal Communication, Organizational Culture and Job Satisfaction - Edowai, Yefri; Hermawan, Andi; Hardhienata, Soewarto (Indonesian Journal of Education and Mathematical Science, 2024)
The unity of teachers with the organization where they work, where the teacher feels that he has an organization and enjoys the conditions of the organization and his work, not only physically but also rationally, emotionally and normatively, so that the teacher feels satisfied and loyal to work in his organization is called teacher engagement. Optimal teacher engagement behavior will have a positive impact on the performance of their work and the madrasah institution. With a sense of love for their work and institution, teachers in carrying out their work work without knowing the time and fully invest themselves and their energy because they are no longer carrying out obligations, but the teaching profession has become a service. in his life. The aim of this research is to find strategies and ways to increase teacher engagement by conducting research on the influence of the variables of self-efficacy, interpersonal communication, organizational support and job satisfaction. This research uses the path analysis method to determine the influence between the variables studied and the SITOREM method for indicator analysis to obtain optimal solutions to increase teacher engagement.